الكشف عن الفطور المتواجدة على(بذور، جذور وترب بادرات) السّرو وأنواع الصّنوبر(البروتي، الكناري والثّمري) في المشتل الحراجي (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2015)
عزل في هذه الدراسة/14/جنساً فطرياً من عينات بذور وبادرات وترب السّرو وأنواع الصّنوبر البروتي؛ الكناري والثّمري جلبت من مشتل الهنادي، تجلت في: Alternaria؛ Rhizoctonia؛Fusarium؛ Chaetomium؛Mucor؛ Phythophtora؛ Rhizopus؛ Aspergillus؛ Penicillium؛ Cladosporium؛ Saccharomyces؛ Sordaria؛ PythiumوTrichoderma، إذ عزلت الأجناس الأثني عشر الأولى من البذور، وظهر الجنسان Alternaria وFusariumعلى بذور كل الأنواع النّباتية ووصل أعلى تردد للأول23.3%وللثاني 36.6%على السّرو، كما عزلت الخمسة أجناس الأولى من جذور البادرات فضلاً عن الجنسPythium، وتردد الجنس Fusarium كذلك على كل الأنواع المدروسة وبنسب مرتفعة بلغ أعلاها 58.5% على الصّنوبر البروتي، ولم يعزل الجنس Rhizoctonia من جذور وبذور السّرو، في حين عزل من جذور وبذور كل أنواع الصّنوبر، أما ترب البادرات فقد عزل منها7 أجناس فطرية ، ثلاثة منها (Alternaria، Aspergillus، Fusarium) عزلت من ترببادرات كل الأنواع النّباتية ، إذ كانت أعلى نسبة مئوية للجنس الأول68.97%من تربة السّرو، وللثاني 22.22% من الصّنوبر الثّمري وللجنسFusarium35.13% من البروتي، كما عزل الجنس Pythiumمن جذور وتربة الصّنوبر البروتي فقط. In this study a total of /14/ fungal genera have been isolated from seeds; seedlings roots and soilsofCypress and Pine species (brutia; canary and stone) samples brought from Hinnade's nursery, and it were: Alternaria; Rhizoctoni; Fusarium; Chaetomium; Mucor; Phythophtora; Rhizopus; Aspergillus; Penicillium; Cladosporium; Saccharomyces; Sordaria; Pytiumand Trichoderma. The first 12 genera were isolated from seeds. Alternaria andFusarium appeared on alldifferent types of plants with the highest frequency of the first genus 23.3% and 36.6% of the second one on cypress. The first 5 genera were isolated from seedlings roots in addition to genus Pythium. And also the Genus Fusariumwas frequented on all study types with high frequencies reached to 58.5%onbrutia.The genusRhizoctoniawas not isolated from seeds and roots of Cypress while it was isolated from seeds and roots of all species of pine./7/ fungal genera were isolated from seedlings soils three of it (Alternaria,Aspergillus,Fusarium) were isolated from the soils of all species of plants with the highest  percentages of the first 68.97% on cypress's soil and 22.22% of the second from stone pine and 35.13%of the genusFusarium from brutia. The highest frequency was for genus Fusarium 35.13% on brutia. The genusPythium was onlyisolated from the seeds and soils of brutia pine.